Cause and chondroprotective effects of prostaglandin E2 secretion during mesenchymal stromal cell chondrogenesis - Schmidt, Sven; Klampfleuthner, Felicia; Renkawitz, Tobias; Diederichs, Solvig (European journal of cell biology, 2024)
Mesenchymal stromal cells (MSCs) that are promising for cartilage tissue engineering secrete high amounts of prostaglandin E2 (PGE2), an immunoactive mediator involved in endochondral bone development. This study aimed to identify drivers of PGE2 and its role in the inadvertent MSC misdifferentiation into hypertrophic chondrocytes. PGE2 release, which rose in the first three weeks of MSC chondrogenesis, was jointly stimulated by endogenous BMP, WNT, and hedgehog activity that supported the exogenous stimulation by TGF-β1 and insulin to overcome the PGE2 inhibition by dexamethasone. Experiments with PGE2 treatment or the inhibitor celecoxib or specific receptor antagonists demonstrated that PGE2, although driven by prohypertrophic signals, exerted broad autocrine antihypertrophic effects. This chondroprotective effect makes PGE2 not only a promising option for future combinatorial approaches to direct MSC tissue engineering approaches into chondral instead of endochondral development but could potentially have implications for the use of COX-2-selective inhibitors in osteoarthritis pain management.